2015
DOI: 10.1007/s10554-014-0585-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of right ventricular functional recovery after acute myocardial infarction by 2D speckle-tracking echocardiography

Abstract: To assess the pattern of right ventricular (RV) functional recovery in a cohort of patients with successful reperfusion of a first episode of acute myocardial infarction (AMI) with 2D speckle-tracking echocardiography and cardiac magnetic resonance imaging (CMR). Ninety-five revascularized AMI patients were prospectively included (56.8 ± 11.1 years, 48 inferior, 47 anterior). RV function was assessed by echocardiography and CMR within the initial 72 h and 6 months later. A RV global strain was calculated while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
(28 reference statements)
2
8
0
3
Order By: Relevance
“…Studies concerning the assessment of RV systolic function after AMI in patients with COPD are lacking. In addition, although the general population frequently show RV functional recovery after AMI, this remains unknown among COPD patients who might already have subclinical damage [69]. Therefore, future research on this subject is required in order to elucidate the influence of COPD on RV function after AMI and the subsequent prognostic implications.…”
Section: Size and Functionmentioning
confidence: 99%
“…Studies concerning the assessment of RV systolic function after AMI in patients with COPD are lacking. In addition, although the general population frequently show RV functional recovery after AMI, this remains unknown among COPD patients who might already have subclinical damage [69]. Therefore, future research on this subject is required in order to elucidate the influence of COPD on RV function after AMI and the subsequent prognostic implications.…”
Section: Size and Functionmentioning
confidence: 99%
“…[21][22][23][24] However, although this modality was initially used to analyze LV function, it is currently applicable to the evaluation of RV function in many A recent study demonstrated that in patients with CSFP, nicorandil treatment raised nitric oxide levels, conditions such as RV myocardial infarction and coronary artery disease. [25][26][27][28] in other LV segments. The authors concluded that the change in nitric oxide and endothelin levels may not be parallel to the change in function of all LV segments.…”
Section: Discussionmentioning
confidence: 98%
“…In acute phase of myocardial infarction, RV strain is more efficient than conventional RV parameters in detecting RV dysfunction. 32 Furthermore, a large retrospective study has demonstrated that RVGLS (with cutoff value ≥−15.5%, area under curve (AUC)=0.742, sensitivity of 73%, specificity of 65%) has an additive predictive value to age while evaluating the 5-year prognosis in patients after inferior ST-segment elevation myocardial infarction (STEMI), particularly in those with preserved LV ejection fraction. 10 Similar results, provided by a meta-analysis of patients with inferior STEMI, associated RV involvement with adverse clinical events that were not due to more extensive infarction of the LV, but related rather to an increased propensity to develop life-threatening ventricular arrhythmias.…”
Section: Potential Role Of Rv Strain In Evaluating Cardiovascular Dmentioning
confidence: 99%